Preparation method of freeze-thawing and salt corrosion resistant plasticizing coating material

CN121895831BActive Publication Date: 2026-10-27安徽交控工程集团有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610042021.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-13
Publication Date
2026-10-27
Estimated Expiration
2046-01-13

AI Technical Summary

Technical Problem

现有涂装材料存在诸多不足:部分抗冻融涂料仅侧重低温稳定性,盐雾侵蚀下易出现涂层起泡、剥落现象;耐盐蚀涂料则多缺乏优异的冻融循环耐受能力,在-20℃至20℃的温差交替环境中,涂层易产生裂纹,导致防护性能失效

Benefits of technology

本发明复合抗冻融剂中碳化硅可提升涂层结构稳定性,硼酸锌与纳米氧化铈协同增强低温韧性,搭配乙二醇的防冻作用,使制备的涂装材料在-20℃至20℃的冻融循环环境中,经过200次循环后仍无裂纹、剥落现象,耐冻融性能远超传统涂装材料。耐盐蚀改性剂中的聚苯并咪唑形成致密防护屏障,阻断氯离子渗透,三乙醇胺与硼酸协同实现阻锈功能;同时改性茶多酚中的活性基团可进一步增强涂层的抗腐蚀能力。采用乙酸乙二醇乙醚酯作为塑化剂,可提升涂层的成膜柔韧性与可塑性,避免施工后出现开裂、起皱问题;双酚A型环氧树脂基料与基材结合紧密,搭配改性茶多酚的增效作用,确保长期服役不易脱落。改性茶多酚的引入不仅增强了涂层的抗氧化、抗老化性能,还提升了材料的环保性,可广泛应用于桥梁、古城墙、海洋工程等多种场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of coating materials, and discloses a preparation method of a freeze-thaw and salt corrosion resistant plasticizing coating material, raw materials of which include bisphenol A type epoxy resin, diethylene triamine, a composite freeze-thaw resistant agent, a salt corrosion resistant modifier, ethylene glycol ethyl ether acetate plasticizer, a composite filler, ethylene glycol and modified tea polyphenol; the prepared coating material has excellent freeze-thaw cycle resistance and salt spray corrosion resistance, and has good plasticizing film forming performance and substrate adhesion; the comprehensive performance is excellent, and the coating material can be widely applied to the protection coating of bridges, ocean engineering, coastal buildings and cultural relic buildings in a freeze-thaw and salt corrosion harsh environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating materials technology, specifically to a method for preparing a freeze-thaw resistant and salt-corrosion resistant plasticizing coating material. Background Technology

[0002] In cold, high-salt-spray environments, such as northern winter road infrastructure, marine engineering structures, coastal buildings, and ancient city walls and other historical buildings, coating materials must simultaneously resist the dual erosion of freeze-thaw cycles and salt corrosion. Existing coating materials have many shortcomings: some freeze-thaw resistant coatings only focus on low-temperature stability, and are prone to blistering and peeling under salt spray corrosion; salt corrosion resistant coatings often lack excellent freeze-thaw cycle resistance, and in environments with alternating temperature differences between -20℃ and 20℃, the coating is prone to cracking, leading to the failure of protective performance.

[0003] For example, concrete bridge railings are constantly exposed to de-icing salt meltwater. Existing coatings, under the combined effects of salt corrosion and freeze-thaw cycles, typically show damage within 1-2 years, requiring frequent repairs. Traditional protective coatings used on stone components such as ancient city walls lack sufficient freeze-thaw resistance, easily peeling off due to frost heave after moisture penetration. They also cannot effectively resist the erosion of salt in the air. Furthermore, most existing coating materials have poor plasticizing properties and insufficient adhesion to the substrate, leading to cracking and wrinkling after application, further reducing protective durability.

[0004] Therefore, developing a method for preparing coating materials that combines excellent freeze-thaw resistance, salt corrosion resistance, and good plasticizing effect, and solving the problem of outstanding single protective performance but insufficient comprehensive performance in existing technologies, has significant engineering application value and market prospects. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a method for preparing a freeze-thaw resistant and salt-corrosion resistant plastic coating material, which has excellent freeze-thaw cycle resistance and salt spray erosion resistance, and at the same time has good plasticizing film-forming properties and substrate adhesion.

[0006] To achieve the above objectives, the present invention employs the following technical solution: To achieve the above objectives, the present invention provides the following technical solution: a freeze-thaw resistant and salt-corrosion resistant plasticizing coating material, comprising the following raw materials in parts by weight: 45-55 parts of bisphenol A type epoxy resin, 2-4 parts of diethylenetriamine, 5-8 parts of composite antifreeze-thaw agent, 3-6 parts of salt-corrosion resistant modifier, 2-5 parts of plasticizer, 2-5 parts of filler, 4-6 parts of ethylene glycol, and 2-3 parts of modified tea polyphenols.

[0007] The composite antifreeze-thaw agent consists of 3-4 parts silicon carbide, 1-2 parts zinc borate, and 1-2 parts nano-cerium oxide. In the above technical solution, zinc borate and nano-cerium oxide work synergistically to reduce the freezing point of the coating, improve low-temperature toughness, resist structural damage caused by freeze-thaw cycles, and further optimize antifreeze performance by combining with ethylene glycol.

[0008] The salt corrosion resistant modifier consists of 1-2 parts polybenzimidazole, 1-2 parts triethanolamine, and 1-2 parts boric acid. The plasticizer is ethylene glycol ethyl ether acetate. The filler is a mixture of 1-2 parts mica powder, 1-2 parts kaolin, and 1 part titanium dioxide.

[0009] Furthermore, the preparation method of the modified tea polyphenols is as follows: S1. Add 4-vinylbenzoyl chloride to N,N-dimethylformamide solvent, stir and disperse, then add 3-(dimethylamino)-1-propanethiol and benzoin dimethyl ether photoinitiator, irradiate with 365nm ultraviolet light at 25-40℃ for 2-3h, centrifuge, wash and dry to obtain tertiary amine-modified benzoyl chloride; S2. Add 2-2.1 g of cashew phenol to 5-5.5 mL of 1,2-bromoethane, then add 0.51-0.52 g of potassium hydroxide, react at 65-75 °C, and after the reaction is completed, separate by column chromatography to obtain intermediate 1; S3. Add 1.1-1.2 mmol of tertiary amine-modified benzoyl chloride and 1.3-1.4 mmol of intermediate 1 to 45-55 mL of N,N-dimethylformamide solvent, stir and mix, react at 80-85 °C, distill under reduced pressure after reaction, filter, and dry to obtain modified cashew phenol. S4. Add modified cashew phenol and tea polyphenol to ethyl acetate, stir and mix, continue to add pyridine catalyst, react at 65-70℃ for 6-7 h, wash and dry after reaction to obtain modified tea polyphenol; In the above reaction process, a four-step reaction method was used to prepare modified tea polyphenols. First, tertiary amine-modified benzoyl chloride was prepared by UV initiation. Then, intermediate 1 was obtained by cashew phenol alkylation reaction. The two were then synthesized by quaternization reaction to synthesize modified cashew phenol. Finally, modified tea polyphenols were generated by esterification reaction with tea polyphenols under pyridine catalysis. The reaction temperature, time and material ratio were precisely controlled in this process to ensure that the active groups of the product were fully exposed.

[0010] Further, in S1, the ratio of N,N-dimethylformamide solvent, 4-vinylbenzoyl chloride, 3-(dimethylamino)-1-propanethiol, and benzoin dimethyl ether photoinitiator is 50-55 mL: 1.4-1.5 g: 1 g: 0.02-0.024 g.

[0011] Furthermore, the reaction time in S2 is 3-4 hours.

[0012] Furthermore, the reaction time in S3 is 6-7 hours.

[0013] Furthermore, the ratio of ethyl acetate, modified cashew phenol, tea polyphenols, and pyridine catalyst in S4 is 40-50 mL: 1-1.1 mmol: 2-3 mmol: 0.01-0.015 g.

[0014] Furthermore, the preparation method of the freeze-thaw resistant and salt-corrosion resistant plasticizing coating material is as follows: adding bisphenol A type epoxy resin, diethylenetriamine, composite antifreeze agent, salt-corrosion resistant modifier, plasticizer, filler, ethylene glycol, and modified tea polyphenols into a stirrer and stirring to obtain the freeze-thaw resistant and salt-corrosion resistant plasticizing coating material.

[0015] Furthermore, the stirring time is 5-10 minutes.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: In this invention, silicon carbide in the composite antifreeze agent enhances the structural stability of the coating, while zinc borate and nano-cerium oxide synergistically enhance low-temperature toughness. Combined with the antifreeze effect of ethylene glycol, the prepared coating material exhibits no cracking or peeling after 200 cycles in a freeze-thaw cycle environment ranging from -20°C to 20°C, demonstrating freeze-thaw resistance far exceeding that of traditional coating materials. The polybenzimidazole in the salt corrosion modifier forms a dense protective barrier, blocking chloride ion penetration, while triethanolamine and boric acid synergistically achieve rust inhibition. Simultaneously, the active groups in the modified tea polyphenols further enhance the coating's corrosion resistance. The use of ethylene glycol ethyl ether as a plasticizer improves the film-forming flexibility and plasticity of the coating, preventing cracking and wrinkling after application. The bisphenol A type epoxy resin binds tightly to the substrate, and the synergistic effect of the modified tea polyphenols ensures long-term service without easy peeling. The introduction of modified tea polyphenols not only enhances the anti-oxidation and anti-aging properties of the coating, but also improves the environmental friendliness of the material, making it widely applicable in various scenarios such as bridges, ancient city walls, and marine engineering. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] 50nm cerium oxide nanoparticles.

[0019] Example 1 Preparation of modified tea polyphenols: S1. Add 1.4 g of 4-vinylbenzoyl chloride to 50 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of 3-(dimethylamino)-1-propanethiol and 0.02 g of benzoin dimethyl ether photoinitiator, irradiate with 365 nm ultraviolet light at 25 °C for 2 h, centrifuge, wash and dry to obtain tertiary amine-modified benzoyl chloride; S2. Add 2g of cashew phenol to 5mL of 1,2-bromoethane, add 0.51g of potassium hydroxide, react at 65℃ for 3h, and then separate by column chromatography to obtain intermediate 1; S3. Add 1.1 mmol of tertiary amine-modified benzoyl chloride and 1.3 mmol of intermediate 1 to 45 mL of N,N-dimethylformamide solvent, stir and mix, react at 80 °C for 6 h, distill under reduced pressure, filter, and dry to obtain modified cashew phenol; S4. Add 1 mmol of modified cashew phenol and 2 mmol of tea polyphenol to 40 mL of ethyl acetate, stir and mix, add 0.01 g of pyridine catalyst, react at 65 °C for 6 h, wash and dry after reaction to obtain modified tea polyphenol.

[0020] Preparation of freeze-thaw resistant and salt corrosion resistant plasticized coating material: Raw material formula (parts by weight): 45 parts of bisphenol A type epoxy resin, 2 parts of diethylenetriamine, 5 parts of composite antifreeze-thaw agent (3 parts of silicon carbide, 1 part of zinc borate, 1 part of nano cerium oxide), 3 parts of salt corrosion resistant modifier (1 part of polybenzimidazole, 1 part of triethanolamine, 1 part of boric acid), 2 parts of plasticizer, 3 parts of filler (1 part of mica powder, 1 part of kaolin, 1 part of titanium dioxide), 4 parts of ethylene glycol, and 2 parts of modified tea polyphenols.

[0021] Add all raw materials to a mixer and stir for 5 minutes to obtain a freeze-thaw resistant and salt-corrosion resistant plastic coating material.

[0022] Example 2 Preparation of modified tea polyphenols: S1. Add 1.45 g of 4-vinylbenzoyl chloride to 52 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of 3-(dimethylamino)-1-propanethiol and 0.022 g of benzoin dimethyl ether photoinitiator, irradiate with 365 nm ultraviolet light at 30 °C for 2.5 h, centrifuge after the irradiation, wash and dry to obtain tertiary amine-modified benzoyl chloride; S2. Add 2.05g of cashew phenol to 5.2mL of 1,2-bromoethane, add 0.515g of potassium hydroxide, react at 70℃ for 3.5h, and then separate by column chromatography to obtain intermediate 1; S3. Add 1.15 mmol of tertiary amine-modified benzoyl chloride and 1.35 mmol of intermediate 1 to 50 mL of N,N-dimethylformamide solvent, stir and mix, react at 82 °C for 6.5 h, distill under reduced pressure, filter, and dry to obtain modified cashew phenol; S4. Add 1.05 mmol of modified cashew phenol and 2.5 mmol of tea polyphenol to 45 mL of ethyl acetate, stir and mix, add 0.012 g of pyridine catalyst, react at 68 °C for 6.5 h, wash and dry after reaction to obtain modified tea polyphenol.

[0023] Preparation of freeze-thaw resistant and salt corrosion resistant plasticized coating material: Raw material formula (parts by weight): 50 parts bisphenol A type epoxy resin, 3 parts diethylenetriamine, 6.5 parts composite antifreeze-thaw agent (3.5 parts silicon carbide, 1.5 parts zinc borate, 1.5 parts nano cerium oxide), 4.5 parts salt corrosion resistant modifier (1.5 parts polybenzimidazole, 1.5 parts triethanolamine, 1.5 parts boric acid), 3.5 parts plasticizer, 4 parts filler (1.5 parts mica powder, 1.5 parts kaolin, 1 part titanium dioxide), 5 parts ethylene glycol, 2.5 parts modified tea polyphenols.

[0024] Add all raw materials to a mixer and stir for 10 minutes to obtain a freeze-thaw resistant and salt-corrosion resistant plastic coating material.

[0025] Example 3 Preparation of modified tea polyphenols: S1. Add 1.5 g of 4-vinylbenzoyl chloride to 55 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of 3-(dimethylamino)-1-propanethiol and 0.024 g of benzoin dimethyl ether photoinitiator, irradiate with 365 nm ultraviolet light at 40 °C for 3 h, centrifuge after the irradiation, wash and dry to obtain tertiary amine-modified benzoyl chloride; S2. Add 2.1g of cashew phenol to 5.5mL of 1,2-bromoethane, add 0.52g of potassium hydroxide, react at 75℃ for 4h, and then separate by column chromatography to obtain intermediate 1; S3. Add 1.2 mmol of tertiary amine-modified benzoyl chloride and 1.4 mmol of intermediate 1 to 55 mL of N,N-dimethylformamide solvent, stir and mix, react at 85 °C for 7 h, distill under reduced pressure, filter, and dry to obtain modified cashew phenol; S4. Add 1.1 mmol of modified cashew phenol and 3 mmol of tea polyphenol to 50 mL of ethyl acetate, stir and mix, add 0.015 g of pyridine catalyst, react at 70 °C for 7 h, wash and dry after reaction to obtain modified tea polyphenol.

[0026] Preparation of freeze-thaw resistant and salt corrosion resistant plasticized coating material: Raw material formula (parts by weight): 55 parts of bisphenol A type epoxy resin, 4 parts of diethylenetriamine, 8 parts of composite antifreeze-thaw agent (4 parts of silicon carbide, 2 parts of zinc borate, 2 parts of nano cerium oxide), 6 parts of salt corrosion resistant modifier (2 parts of polybenzimidazole, 2 parts of triethanolamine, 2 parts of boric acid), 5 parts of plasticizer, 5 parts of filler (2 parts of mica powder, 2 parts of kaolin, 1 part of titanium dioxide), 6 parts of ethylene glycol, and 3 parts of modified tea polyphenols.

[0027] Add all raw materials to a mixer and stir for 8 minutes to obtain a freeze-thaw resistant and salt-corrosion resistant plastic coating material.

[0028] Example 4 Preparation of modified tea polyphenols: S1. Add 1.4 g of 4-vinylbenzoyl chloride to 50 mL of N,N-dimethylformamide solvent, stir and disperse, then add 1 g of 3-(dimethylamino)-1-propanethiol and 0.02 g of benzoin dimethyl ether photoinitiator, irradiate with 365 nm ultraviolet light at 25 °C for 2 h, centrifuge, wash and dry to obtain tertiary amine-modified benzoyl chloride; S2. Add 2g of cashew phenol to 5mL of 1,2-bromoethane, add 0.51g of potassium hydroxide, react at 65℃ for 3h, and then separate by column chromatography to obtain intermediate 1; S3. Add 1.15 mmol of tertiary amine-modified benzoyl chloride and 1.35 mmol of intermediate 1 to 50 mL of N,N-dimethylformamide solvent, stir and mix, react at 82 °C for 6.5 h, distill under reduced pressure, filter, and dry to obtain modified cashew phenol; S4. Add 1.1 mmol of modified cashew phenol and 3 mmol of tea polyphenol to 50 mL of ethyl acetate, stir and mix, add 0.015 g of pyridine catalyst, react at 70 °C for 7 h, wash and dry after reaction to obtain modified tea polyphenol.

[0029] Preparation of freeze-thaw resistant and salt corrosion resistant plasticized coating material: Raw material formula (parts by weight): 55 parts of bisphenol A type epoxy resin, 4 parts of diethylenetriamine, 8 parts of composite antifreeze-thaw agent (4 parts of silicon carbide, 2 parts of zinc borate, 2 parts of nano cerium oxide), 6 parts of salt corrosion resistant modifier (2 parts of polybenzimidazole, 2 parts of triethanolamine, 2 parts of boric acid), 5 parts of plasticizer, 5 parts of filler (2 parts of mica powder, 2 parts of kaolin, 1 part of titanium dioxide), 6 parts of ethylene glycol, and 3 parts of modified tea polyphenols.

[0030] Add all raw materials to a mixer and stir for 8 minutes to obtain a freeze-thaw resistant and salt-corrosion resistant plastic coating material.

[0031] Comparative Example 1 Compared with Example 2, tea polyphenols were used instead of modified tea polyphenols, while the other raw material formulations and preparation steps were the same.

[0032] Comparative Example 2 Compared with Example 2, 8 parts of nano-cerium oxide were used instead of the composite antifreeze agent, while the other raw material formulations and preparation steps were the same.

[0033] All test samples used the coating materials prepared in Examples 1-4 and Comparative Examples 1-2 of this invention. The substrates for performance testing were mortar test panels (120mm×40mm×10mm, 150mm×70mm×20mm) and concrete test blocks (100mm×100mm×100mm). Mortar test slab: PO 42.5 cement and ISO standard sand were mixed in a mass ratio of water:cement:sand = 1:1:6 to characterize the properties of the low-strength mortar layer on the surface of the guardrail. After mixing, the slab was poured into a metal mold for molding.

[0034] Concrete specimens: Referring to JTG 3420—2020 and T 0551—2020, Cement Concrete Specimen Preparation and Hardening Cement Concrete Field Sampling Method, concrete specimens with a strength grade of C40 and dimensions of 100 mm × 100 mm × 100 mm were designed and prepared.

[0035] Before coating, sand off the surface laitance, wipe clean with anhydrous ethanol, and let it air dry until there is no moisture on the surface. The coating method is scraping, and the coating thickness is controlled at 150±20μm. After coating, cure for 7 days in a standard environment (temperature 23±2℃, relative humidity 50±5%) to ensure complete curing before conducting various performance tests.

[0036] Surface drying time: Refer to GB / T 1728-2020 "Determination of drying time of paint film and putty film", and use the cotton ball blowing method to determine the surface drying time.

[0037] Test Procedure: Gently place a loosely rubbed cotton ball on the surface of the coating to be tested. Maintain a horizontal distance of approximately 10-15 cm between the operator's mouth and the cotton ball, and gently blow on the cotton ball horizontally. When the cotton ball can be blown away from the coating surface without leaving any cotton fibers or obvious contact marks, the coating is considered to have reached a dry state. Record the time interval from the start of coating to the first time the above conditions are met as the surface drying time (t). s ).

[0038] Crack tracking test: Testing equipment: Universal testing machine Test steps: (1) Draw a 5mm deep groove on the surface of the molded specimen (120mm×40mm×10mm). Break the concrete specimen along the groove, place a steel plate on the side with the groove, seal the two ends of the specimen 30mm apart, leaving an area of ​​60mm×40mm to be coated. (2) After applying the coating to the reserved area, cure for 14 days at 23℃±2℃ and 50%±5% humidity; fix the uncoated parts at both ends of the specimen on the upper and lower clamps of the universal tensile testing machine. (3) Start the testing machine and load at a uniform speed of 5mm / min. At this time, the substrate has been pre-broken, and the tensile displacement will be converted into the extension deformation of the coating. (4) Observe the coating status in real time. When the first through crack appears on the coating surface or the coating is completely broken, stop the test immediately and record the maximum displacement value (L) at this time, which is the maximum crack following displacement of the coating.

[0039] Salt freeze-thaw resistance test: Testing equipment: rapid freeze-thaw test chamber (temperature control accuracy ±1℃), electronic balance (accuracy 0.01g), compressive strength tester; Test steps: (1) Select 3 samples of the coating after the concrete substrate has been cured, number them and weigh the initial mass (m0), and test the initial compressive strength (f0); (2) Put the samples into the freeze-thaw test chamber, set the freezing temperature to -20℃ and the freezing time to 4h, take them out and put them in salt water at 20℃ for 4h to complete one freeze-thaw cycle; (3) After completing 200 freeze-thaw cycles, take out the samples and place them in a standard environment for 24h to observe whether cracks, peeling, blistering and other phenomena appear on the coating surface; (4) Weigh the mass of the sample after the cycle (m1) and calculate the mass loss rate: mass loss rate = (m0-m1) / m0×100%; (5) Test the compressive strength (f1) of the sample after the cycle and calculate the strength loss rate: strength loss rate = (f0-f1) / f0×100%.

[0040] Neutral salt spray resistance test: Testing equipment: Salt spray aging test chamber Test Procedure: The test chamber temperature was set to 35.0°C, and the saturation tank temperature was set to 45°C. A 5wt% NaCl solution was used for the salt spray test. The atomization mode was set to continuous, with a 1-minute atomization interval followed by a 59-minute pause, and a total time of 1500 hours. After the salt spray experiment, the samples were rinsed with deionized water, and the corrosion of different samples was compared.

[0041] Adhesion (concrete substrate): Testing equipment: Digital display adhesive strength tester Test steps: (1) Clean the coating surface and the bottom of the test spindle; (2) Apply a thin layer of high-strength adhesive evenly to the bottom of the test spindle; (3) Press the test column onto the coating surface, keeping it vertical, squeeze out excess adhesive and wipe it clean, and allow it to fully cure within the specified temperature and time according to the requirements of the adhesive; (4) Use a special cutting tool to cut through the coating to the substrate around the spindle to eliminate the lateral support of the surrounding coating; (5) Align the sleeve of the tensile tester with and hold the spindle in place, ensuring alignment. Apply a pull-out force slowly and evenly, and the instrument will record the peak force value during the pull-out process. Stop loading immediately after the spindle is pulled out; (6) After recording the peak tensile force value during pull-out, the instrument will automatically or by calculation give the adhesion strength. Table 1: Performance Tests

[0042] As shown in Table 1, the composite antifreeze agent is the core guarantee for freeze-thaw resistance and low-temperature toughness: Comparative Example 2, lacking this synergistic system, showed a significant decrease in freeze-thaw resistance and plasticizing properties. Data shows that the mass loss rate (0.6%) and strength loss rate (38%) of Comparative Example 2 were 4.0 times and 1.8 times that of Example 2, respectively. More importantly, its crack following displacement, characterizing low-temperature toughness, was only 9.77 mm, far lower than the 28.56 mm of Example 2, proving that the synergistic effect of the three components can effectively resist structural damage caused by freeze-thaw cycles—silicon carbide improves the physical stability of the coating's microstructure, zinc borate and nano-cerium oxide significantly enhance ductility at low temperatures, and ethylene glycol further lowers the freezing point, thereby preventing brittle cracking of the coating.

[0043] Modified tea polyphenols exhibit significant thickening and antifreeze-enhancing effects: Compared to Example 2, Comparative Example 1 (using ordinary tea polyphenols instead of modified tea polyphenols) showed a comprehensive decline in performance, with its bond strength decreasing from 1.37 MPa to 1.17 MPa, and its freeze-thaw stability deteriorating, resulting in an 80% increase in mass loss rate and a 51.7% increase in strength loss rate. The underlying mechanism is speculated to be that the modified tea polyphenols introduce active groups, effectively improving compatibility with the epoxy resin matrix. This not only optimizes the internal bonding force of the coating to reduce stress concentration but also significantly enhances the "anchoring" effect of the coating on the concrete substrate.

[0044] Example 3 shows the best performance: because the composite antifreeze and modified tea polyphenols are in the highest ratio (8 parts and 3 parts), the synergistic effect of each component reaches its peak, so that while maintaining the lowest mass loss rate (0.12%) and strength loss rate (20.7%), it achieves the highest crack following displacement (30.10 mm) and bonding strength (1.53 MPa), and has excellent protective durability, high plasticity and strong adhesion.

[0045] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0046] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

[0047] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments.

Claims

1. A freeze-thaw resistant and salt-corrosion resistant plasticizing coating material, characterized in that, The raw materials include the following parts by weight: 45-55 parts of bisphenol A type epoxy resin, 2-4 parts of diethylenetriamine, 5-8 parts of composite antifreeze-thaw agent, 3-6 parts of salt corrosion resistant modifier, 2-5 parts of plasticizer, 3-5 parts of filler, 4-6 parts of ethylene glycol, and 2-3 parts of modified tea polyphenols. The composite antifreeze-thaw agent consists of 3-4 parts silicon carbide, 1-2 parts zinc borate, and 1-2 parts nano-cerium oxide. The salt corrosion resistant modifier consists of 1-2 parts polybenzimidazole, 1-2 parts triethanolamine, and 1-2 parts boric acid. The plasticizer is ethylene glycol ethyl ether acetate. The filler is a mixture of 1-2 parts mica powder, 1-2 parts kaolin, and 1 part titanium dioxide; The method for preparing the modified tea polyphenols is as follows: S1. Add 4-vinylbenzoyl chloride to N,N-dimethylformamide solvent, stir and disperse, then add 3-(dimethylamino)-1-propanethiol and benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 25-40℃ for 2-3 hours, centrifuge after the irradiation, wash and dry to obtain tertiary amine-modified benzoyl chloride; S2. Add cashew phenol to 1,2-dibromoethane, then add potassium hydroxide, react at 65-75℃, and after the reaction is completed, separate by column chromatography to obtain intermediate 1; S3. Add tertiary amine-modified benzoyl chloride and intermediate 1 to N,N-dimethylformamide solvent, stir and mix, react at 80-85℃, distill under reduced pressure after reaction, filter, dry, and obtain modified cashew phenol; S4. Add modified cashew phenol and tea polyphenol to ethyl acetate, stir and mix, continue to add pyridine catalyst, react at 65-70℃ for 6-7 h, wash and dry after reaction to obtain modified tea polyphenol.

2. The freeze-thaw resistant and salt-corrosion resistant plasticizing coating material according to claim 1, characterized in that, In S1, the ratio of N,N-dimethylformamide solvent, 4-vinylbenzoyl chloride, 3-(dimethylamino)-1-propanethiol, and benzoin dimethyl ether photoinitiator is 50-55 mL: 1.4-1.5 g: 1 g: 0.02-0.024 g.

3. The freeze-thaw resistant and salt-corrosion resistant plasticizing coating material according to claim 1, characterized in that, The reaction time in S2 is 3-4 hours.

4. The freeze-thaw resistant and salt-corrosion resistant plasticizing coating material according to claim 1, characterized in that, The reaction time in S3 is 6-7 hours.

5. The freeze-thaw resistant and salt-corrosion resistant plasticizing coating material according to claim 1, characterized in that, In S4, the ratio of ethyl acetate, modified cashew nut extract, tea polyphenols, and pyridine catalyst is 40-50 mL: 1-1.1 mmol: 2-3 mmol: 0.01-0.015 g.

6. A method for preparing a freeze-thaw resistant and salt-corrosion resistant plasticizing coating material as described in any one of claims 1-5, characterized in that, Bisphenol A type epoxy resin, diethylenetriamine, composite antifreeze-thaw agent, salt corrosion resistant modifier, plasticizer, filler, ethylene glycol, and modified tea polyphenols are added to a mixer and stirred to obtain a freeze-thaw resistant and salt corrosion resistant plasticized coating material.

7. The method for preparing the freeze-thaw resistant and salt-corrosion resistant plasticizing coating material according to claim 6, characterized in that, The stirring time is 5-10 minutes.

Citation Information

Patent Citations

  • Self-repairing anticorrosive coating as well as preparation method and application thereof

    CN119039861A

  • Preparation method and application of UV resin coating

    CN120272099A